Acute Cervical Dystonia Induced by Clebopride - Jin Kyo Choi; Jin Yong Hong (Case Reports in Neurological Medicine)
Antidopaminergic drugs are known to induce extrapyramidal symptoms. Clebopride, a dopamine antagonist, also can produce parkinsonism, tardive dyskinesia, tardive dystonia, hemifacial dystonia, or oculogyric crisis; however, acute dystonic reaction caused by clebopride has not been reported in adults. We report two young men who experienced acute cervical dystonia within a few days of taking clebopride. The patients recovered after discontinuation of the drug. Physicians prescribing clebopride should be aware of the adverse effects of this drug.